Phenotypic and genotypic characterization of H2S‐positive and H2S‐negative strains of Shewanella baltica isolated from spoiled whiting (Merlangius merlangus). (21st August 2014) - Dehaut, A.; Midelet‐Bourdin, G.; Brisabois, A.; Duflos, G.
Abstract Four strains were isolated from a spoiled whiting (Merlangius merlangus). All of them were able to grow aerobically from 4 to 30°C and also able to develop anaerobically in the presence of trimethylamine N‐Oxide (TMAO) at 25°C. Biochemical characterization did not allow identification of the strains species but showed that one of the four strains was unable to produce H2S. Two strains synthetized an ornithine decarboxylase being potential putrescine producers. Results of carbon source use highlighted that the four strains were able to use citrate and d‐sucrose and one strain was not able to use l‐arabinose. Genotypic characterization of the strains thanks to 16S rRNA and gyrB partial gene sequencing led to their identification as members of Shewanella baltica species. These observations suggest that H2S production may not be the most appropriate screening parameter for Shewanella species and further to monitor the development of spoilage flora. Significance and Impact of the Study Shewanella is a complex genus composed of numerous and heterogeneous species. One of them Shewanella baltica has previously been described as one of the most important H2S‐producing bacterial species in iced stored fish and may act as spoilage organism through the reduction of trimethylamine N‐Oxide (TMAO). Four strains of S. baltica were isolated from spoiled whiting (Merlangius merlangus), and description of three H2S‐positive strains and one H2S‐negative strain of S. baltica is highlighted in this short paper. Consequently, H2S production might not be the most appropriate screening parameter to assess the development of spoilage organisms.